Strategic Implementation of Zakat Education in Madrasahs: A Business Model Canvas Approach - Hakim, Miftahur Rahman; Lestari, Azwah Tri; Amanah, Rawdatul; Marjuni, Kamaluddin Nurdin; Dewingga, Zalsa Puja; Juswil, Hafizhan Arhab (LP2M IAIN Palopo, 2024)
The development of zakat potential in fact does not go hand in hand with education and knowledge about zakat. One of the problems is the absence of zakat education curriculum specifically. This research attempts to examine the strategy of zakat education in madrasah. The focus of this research is using BMC (business model canvas) strategy that can be used in non-profit organizations. The method used is qualitative and the source of data obtained by revealing phenomena in the community as an objective secondary data source in the field. Researchers used data triangulation in the form of interviews, observation and documentation in data collection techniques. The results of this study indicate that there are four elements that are important aspects of zakat education in madrasah, namely customer segments, value propositions, key activities and key resources. So that it takes a joint role to implement zakat education in madrasas better.